2017
DOI: 10.1155/2017/4074137
|View full text |Cite
|
Sign up to set email alerts
|

An HTML5-Based Pure Website Solution for Rapidly Viewing and Processing Large-Scale 3D Medical Volume Reconstruction on Mobile Internet

Abstract: This study aimed to propose a pure web-based solution to serve users to access large-scale 3D medical volume anywhere with good user experience and complete details. A novel solution of the Master-Slave interaction mode was proposed, which absorbed advantages of remote volume rendering and surface rendering. On server side, we designed a message-responding mechanism to listen to interactive requests from clients (Slave model) and to guide Master volume rendering. On client side, we used HTML5 to normalize user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For example, if wanting the rendering capacity of the client to reach 30 fps, the server will be required to provide 30 continuous responses and 30 image compressions and network transmissions within 1 second. In our team's preliminary work in [ 9 ], through low-quality 3D navigation, we avoided continuous server response and network load pressure in the interaction process, but that work was only for 3D volume rendering operations. This paper has designed a navigation mode for MPR and MIPs to improve interaction efficiency, which has been recognized by five radiologists.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, if wanting the rendering capacity of the client to reach 30 fps, the server will be required to provide 30 continuous responses and 30 image compressions and network transmissions within 1 second. In our team's preliminary work in [ 9 ], through low-quality 3D navigation, we avoided continuous server response and network load pressure in the interaction process, but that work was only for 3D volume rendering operations. This paper has designed a navigation mode for MPR and MIPs to improve interaction efficiency, which has been recognized by five radiologists.…”
Section: Resultsmentioning
confidence: 99%
“…However, the traditional method has resulted in huge pressure on both the server response and the network feedback. Based on the basic data penetration architecture in Figure 1 , this paper further adopted the “Master-Slave” two-channel interaction [ 9 ] to solve the interactive experience problem of remote rendering technology. The overall structure is shown in Figure 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these medical visualization possibilities have been developed over the years and improved by WebGL's stable release 2.0 in 2017. Similarly, this approach was succeeded by Qiao et al [37] with a website for rapidly viewing, processing, and reconstructing large-scale 3D medical volumes on the mobile internet. As of today, in the medical imaging field, Digital Imaging and Communications (DICOM) is still the de facto standard and is often accompanied by large amounts of metadata with related information about the patient or medical procedures [106].…”
Section: Medical Applicationsmentioning
confidence: 98%
“…In particular, the visualization of multi-modality cardiac data over the Internet can convey a significant amount of image information from various sources into a single and meaningful display [18], [42], [43], and the complementary image can facilitate timely diagnosis and identification of patients in need of surgical management [19], [20]. For instance, Qiao et al [12] proposed an HTML5-based solution to access large-scale 3D cardiac volume, and Arumugham's research group [44] built a user interface to Local Area Network for storing and accessing medical records, while Min et al [14] reported several applications for viewing radiological images remotely. Korzun [6] presented a detailed overview of the applications of the Internet of Things (IoT) in mobile health (mHealth) system for providing patients with customized smart services though Internet.…”
Section: Related Workmentioning
confidence: 99%